Management of screen-detected lung nodules: A Canadian partnership against cancer guidance document. Issue 4 (1st October 2020) - Lam, Stephen; Bryant, Heather; Donahoe, Laura; Domingo, Ashleigh; Earle, Craig; Finley, Christian; Gonzalez, Anne V.; Hergott, Christopher; Hung, Rayjean J.; Ireland, Anne Marie; Lovas, Michael; Manos, Daria; et al.
Abstract: RATIONALE: Appropriate management of low-dose computed tomography (LDCT) screening detected lung nodules will have significant implications for health care resource utilization and minimizing harm from radiation exposure related to imaging studies, invasive procedures and clinically significant distress. OBJECTIVES: We aimed to: provide a practical, evidence-based best practice framework for healthcare professionals (HP) to manage screening LDCT detected lung nodules and identify areas that require future studies. METHODS: The Canadian Partnership Against Cancer and Pan-Canadian Lung Cancer Screening Network (PLCSN) undertook a scientific review of the assessment and management of screening LDCT detected lung nodules. Key messages were derived by consensus through a series of stakeholder meetings to obtain full consensus. MAIN RESULTS: 1) A high standard of LDCT image quality is of importance to determine nodule type, size and growth; 2) Personalized approach to manage screen detected lung nodules based on malignancy probability is a promising approach to decrease resource utilization and minimize risk of screening; 3) Radiologist reports should provide specific guidance for expert and non-expert health care providers regarding the most appropriate next step with a separate lay-language report for screenees tailored to the general result category along with a recommended next step; 4) Diagnostic work-up in centers with multidisciplinary specialized expertise in minimally invasive sampling of pulmonary nodules is recommended to achieve the best possible yield and lowest complications rate; and 5) Common quality indicators in lung nodule management protocols across health jurisdictions provide the opportunity to evaluate and refine management protocols.